Values Reflected in First Language Textbooks of Primary Education in West Bengal - Ankur Nandi; Tarini Hader; Tapash Das (Athena: Journal of Social, Culture and Society, 2024)
Textbooks function as catalysts for societal change, influencing students’ values, beliefs, and cultural awareness from their primary level of education. Textbooks serve as key learning resources for students which significantly influences students’ character development. The creation of textbooks reflecting values is essential, and achieving this goal requires a comprehensive analysis of textbooks. The objectives of the study are focused on examining values are represented in the text and images found within Bengali language textbooks of Primary Education Board, School Education Departments, govt. of West Bengal, India was the publisher of the textbook. A Bengali textbook named “Patabahar” of class IV of the West Bengal Board of Primary Education has been chosen through the purposive sampling technique as a sample in this study. This study used qualitative and documentary research methods through content analysis. The findings demonstrate that social values, moral values, environmental values, and Personal values, emotional values, cultural values are more reflected and spiritual, aesthetic, humanistic, economic, historical, civic, peace, national, cognitive values were minimally reflected across the textbooks. The study results provide a basis for state or national policy changes that promote values-balanced content in educational media and ensure the development and implementation of guidelines that are beneficial to the development of textbook development agencies. Also, helpful for textbook authors and teachers in developing a value-alignment curriculum and creating more inclusive, culturally sensitive, and ethically grounded visual materials